2005
DOI: 10.1176/appi.ajp.162.6.1090
|View full text |Cite
|
Sign up to set email alerts
|

Lower Prepulse Inhibition in Children With the 22q11 Deletion Syndrome

Abstract: Objective-The 22q11 deletion syndrome is associated with a range of possible physical anomalies, probable ongoing learning disabilities, and a specific constellation of neuropsychological deficits, including impairments in selective and executive visual attention, working memory, and sensorimotor functioning. It has been estimated that 25% of the children with 22q11 deletion syndrome go on to develop schizophrenia in late adolescence or adulthood. This is of urgent concern. Specification of early brain network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
83
4
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 50 publications
8
83
4
1
Order By: Relevance
“…29 The PRODH gene encodes proline dehydrogenase, which is key in the production of glutamate; glutamate in turn directly influences GABA production and release. The COMT gene encodes catechol-Omethyltransferase, which catabolizes excess brain dopamine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…29 The PRODH gene encodes proline dehydrogenase, which is key in the production of glutamate; glutamate in turn directly influences GABA production and release. The COMT gene encodes catechol-Omethyltransferase, which catabolizes excess brain dopamine.…”
Section: Discussionmentioning
confidence: 99%
“…The comparability of this method to the electromyographic (EMG) method was previously demonstrated and discussed. 29,37 Auditory stimuli for the PPI paradigm were presented binaurally through Sony MDR-V6 headphones nested over the LED headband. A background white noise of 50 db (A scale) was present before, in between, and after all trial stimuli presentations.…”
Section: Apparatus and Stimulimentioning
confidence: 99%
See 1 more Smart Citation
“…One indication supporting the former possibility is the recent report that PPI is normal in effectively treated, non-manic patients with childhood bipolar disorder (Rich et al, 2005). In additional studies prompted in part by suggested genetic contributions to schizophrenia or related disorders, deficits in PPI have also been identified in children with 22q deletion syndrome (Sobin et al, 2005), young persons with Fragile X syndrome (Frankland et al, 2004), and adults with Asperger's syndrome (McAlonan et al, 2002), seizure disorder (Pouretemad et al, 1998), or Lewy body dementia (Perriol et al, 2005).…”
Section: Sensorimotor Gating Deficits In Psychiatric Disordersmentioning
confidence: 99%
“…Compared with matched controls, PPI is deficient in patients with schizophrenia (e.g., Braff et al 1978;Swerdlow et al 2006), Huntington's disease Valls-Sole et al 2004), obsessive-compulsive disorder (OCD) Hoenig et al 2005;Ahmari et al 2012), nocturnal enuresis (Ornitz et al 1992), Asperger's syndrome (McAlonan et al 2002), 22q11 syndrome (Sobin et al 2005), Kleinfelter syndrome (Van Rijn et al 2011), fragile X syndrome (Frankland et al 2004), blepharospasm (Gomez-Wong et al 1998, and Tourette syndrome (Castellanos et al 1996;Swerdlow et al 2001b).…”
Section: The Evolution Of Prepulse Inhibition As a Validated Animal Mmentioning
confidence: 99%